PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM CORPORATE SOCIAL RESPONSIBILITY PT. PERTAMINA (PERSERO) DPPU AHMAD YANI (STUDI KASUS PROGRAM CSR KELOMPOK USAHA BINAAN PERTAHARJO KELURAHAN TAMBAKHARJO KOTA SEMARANG) - Rasyid, Khairuddin -; Taufiq, Ahmad - (Journal of Politic and Government Studies, 2021)
The vulnerability of the welfare experienced by the community requires the government to intervene in improving the welfare of the community, one of which is through the CSR program, the program is a concept where companies integrate social and environmental problems in the company's business operations and in the company's interactions with their stakeholders voluntarily. In line with the recommendations of the Semarang City Government, the company participates in programs to improve community welfare through the utilization of CSR funds according to the law, the company carries out its social responsibility with a development model that is aimed directly at the community and emphasizes empowerment. In this study, there were four parties involved in the CSR partnership of the community empowerment program, namely PT. Pertamina (Persero) DPPU Ahmad Yani as the initiator of the program, Tambakharjo Village Government as implementing regulations, Undip academics as drafters in this program, and the community as subjects of the CSR program. The research method used by researchers is a descriptive qualitative research method, it has the basic purpose of knowing the CSR implementation partnership process and explaining how the community empowerment process is. The results of this study are related to the process and implementation of partnerships in CSR community empowerment programs implemented by PT. Pertamina (Persero) DPPU Ahmad Yani in 2019. Researchers tried to dig up data on the CSR partnership process through mapping actors and identifying partnership patterns that were applied, as well as in partnerships as a strategy for community empowerment. CSR Program of PT. Pertamina (Persero) DPPU Ahmad Yani can be said to be successful, referring to the indicators of the success of the CSR partnership in the community empowerment program